Avoiding and repropping from taxation as ways of managing the consumer’s tax portfolio – about threats and contraindications - Abramczyk, Damian (Journal of Finance and Financial Law, 2019)
The consumer’s primary goal is spending previously earned money. Earned income is the main way to keep him and his relatives. However, these, in their definition, fulfill many other, equally important functions – their discharged part supplies the State Treasury budget, which, through redistribution, is used for the activities important for the public. Very often this is met with disapproval and general tax reluctance. The article below will present the most important functions of the tax system, based on the system in effect in the territory of the Republic of Poland. It also includes taxpayers’ reactions to the current legal and economic situation and will reveal the most basic ways to avoid and evade taxation.